The Role of Teachers in the Development of Digital Literacy - Desniyanti, Desniyanti (PPSDP International Journal of Education, 2025)
This study aims to identify the role of teachers in developing students’ digital literacy at the secondary school level. Digital literacy is an important skill in this technological era, which includes not only technical skills in using devices but also critical skills to sort information and apply ethical values ​​in the use of technology. This study uses a qualitative approach with in-depth interview methods, classroom observations, and document analysis to explore the roles, challenges, and needs of collaboration in developing digital literacy. The results of the study show that teachers have three main roles in digital literacy: as facilitators who support students’ technical and critical abilities, as digital ethics guides who instill a responsible attitude, and as technology mediators who help students with limited access or skills. However, teachers face various challenges, including limited digital literacy training, minimal technology infrastructure in schools, and a lack of supportive education policies. These challenges require stronger collaboration between teachers, schools, parents, and the government. Greater support from all parties is needed to create a conducive and adequate learning environment for the development of students’ digital literacy. In conclusion, effective digital literacy development requires continuous and collaborative support so that students are ready to face the challenges of the digital world wisely and productively.